A giant short arm of no. 21 chromosome in mother of 21/21 translocation mongol. Issue 5 (October 1976) - Tuncbilek, E; Bobrow, M; Clarke, G; Taysi, K
Abstract : An extreme variation of the short arm of no. 21 chromosome in the mother of a 21/21 translocation mongol is described. The possible relation between the very long short arm of chromosome no. 21 in the mother and a centric fusion type of translocation mongolism in the offspring is discussed.